2010
DOI: 10.1175/2010jhm1254.1
|View full text |Cite
|
Sign up to set email alerts
|

Pacific Decadal Oscillation Climate Variability and Temporal Pattern of Winter Flows in Northwestern North America

Abstract: There is growing concern about the effects of large-scale oceanic atmospheric climate variability, such as the Pacific decadal oscillation (PDO), on regional hydrology and water resources. In this paper, the effects of PDO on temporal patterns of winter (January-March) flow in northwestern North America (NWNA), which is believed to be a PDO-sensitive region, is studied for the period 1943-2007 using daily streamflow data from a much larger set of 179 stations, compared to previous studies in which only smaller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…For example, Hamlet and Lettenmaier (2007) North America and Europe, and found that the statistically significant trends detected were almost the same as the ones expected by chance, with changes in major floods dominated instead by climate patterns such as the PDO and AMO. In north-western North America the PDO is found to have an effect on winter river flows, with flows being higher during the warm PDO phase (and vice versa) (Khaliq and Gachon, 2010). The PDO is also known to influence flows in Alaska (Hodgkins, 2009;Neal et al, 2002), where its signal does not change significantly on annual river flows, but it does on monthly and seasonal time scales, with warm PDO winter river flows being higher than the cold PDO ones (Neal et al, 2002).…”
Section: Fluvial Flooding and Modes Of Climate Variabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Hamlet and Lettenmaier (2007) North America and Europe, and found that the statistically significant trends detected were almost the same as the ones expected by chance, with changes in major floods dominated instead by climate patterns such as the PDO and AMO. In north-western North America the PDO is found to have an effect on winter river flows, with flows being higher during the warm PDO phase (and vice versa) (Khaliq and Gachon, 2010). The PDO is also known to influence flows in Alaska (Hodgkins, 2009;Neal et al, 2002), where its signal does not change significantly on annual river flows, but it does on monthly and seasonal time scales, with warm PDO winter river flows being higher than the cold PDO ones (Neal et al, 2002).…”
Section: Fluvial Flooding and Modes Of Climate Variabilitymentioning
confidence: 99%
“…America, Europe and central Asia (Lee et al, 2018). Moreover, when PDO is positive, the central and south-western USA tends to experience flooding during all the seasons, except during winter (Mallakpour and Villarini, 2016;Tootle et al, 2005), when increased streamflow are observed in north-western North America (Hodgkins, 2009;Khaliq and Gachon, 2010;Neal et al, 2002).…”
Section: Fluvial Flooding and Modes Of Climate Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, several recent studies in North America have modelled the non-stationarity of precipitation and streamflow using climate indices. The most used climate indices in this context are El Nino Southern Oscillation (ENSO) (e.g., Regonda et al, 2005;Cannon, 2010;Nasri et al, 2013), Pacific Decadal Oscillation (PDO) (e.g., Brabets and Walvoord, 2009;Khaliq and Gachon, 2010;Cannon, 2010;Nasri et al, 2013), Atlantic Multi-decadal Oscillation (AMO) (Teegavarapu et al, 1969) and North Atlantic Oscillation (NAO) (Hurrell and Van Loon, 1997). To our knowledge, no studies have previously studied streamflow extremes using nonparametric quantile regression incorporating B-Spline functions.…”
Section: Introductionmentioning
confidence: 99%
“…In western North America, large interannual and interdecadal variability is a common climate feature (see Bonsal & Shabbar, ) and is associated with extreme shifts in low‐ and high‐flow events of many river systems in this region (e.g., Burn, ; Déry, Hernández‐Henríquez, Owens, Parkes, & Petticrew, ; Doney & Sailley, ; Gobena, Weber, & Fleming, ; Mauget, ; Sauchyn, Vanstone, & Perez‐Valdivia, ), including the SSR (e.g., Axelson, Sauchyn, & Barichivich, ; Marchildon et al, ). Such climate variability is mainly attributed to various large‐scale climate circulation patterns (see Bonsal & Shabbar, ; Shabbar & Bonsal, , ; Shabbar, Bonsal, & Khandekar, ; Shabbar & Khandekar, ) with the dominant streamflow mode in the SSR being the Pacific Decadal Oscillation (PDO; see, e.g., Bonsal et al, ; Fleming & Whitfield, ; Khaliq & Gachon, ; St. Jacques et al, ; Whitfield, Moore, Fleming, & Zawadzki, ). The PDO is a large‐scale interdecadal climate variability index, with negative and positive phases, which is linked to North Pacific sea surface temperature anomalies (Bonsal, Shabbar, & Higuchi, ; Mantua & Hare, ; Minobe, ).…”
Section: Introductionmentioning
confidence: 99%